CADANGAN KARBON TERSIMPAN PADA TEGAKAN CEMARA LAUT (Casuarina equisetifolia L) - Helmud Putra Anas Hutasoit; Delvian Delvian; Kansih Sri Hartini (Program studi Kehutanan USU, 2015)
This research aimed to estimate the carbon stocks in Casuarina equisetifolia L according to the habitat and to compare the carbon stocks of Casuarina equisetifolia L on two different locations. The method used to calculate carbon stocks is non-destructive method. The result showed that the amount of carbon stocks in Sri Mersing Beach is 18,524 ton/ha while in the Gudang SCM PT.Pertamina Beach is 11,45 ton/ha. The average of carbon stocks in Sri Mersing Beach is 154,36 kg/tree while in the Gudang SCM PT. Pertamina Beach is 69,57 kg/tree . The differences between the amount of carbon stocks in this two research areas are caused by the density of trees and silviculture factor.Key words : Carbon stock, Casuarina equisetifolia L, Sri Mersing Beach, Gudang SCM PT. Pertamina Beach.